The long wave of COVID-19: a case report using Imagery Rehearsal Therapy for COVID-19-related nightmares after admission to intensive care unit - Rapelli, Giada; Varallo, Giorgia; Scarpelli, Serena; Pietrabissa, Giada; Musetti, Alessandro; Plazzi, Giuseppe; Franceschini, Christian; Castelnuovo, Gianluca (Frontiers in Psychology, 2023)
Introduction The COVID-19 pandemic caused several psychological consequences for the general population. In particular, long-term and persistent psychopathological detriments were observed in those who were infected by acute forms of the virus and need specialistic care in the Intensive Care Unit (ICU). Imagery rehearsal therapy (IRT) has shown promising results in managing nightmares of patients with different traumas, but it has never been used with patients admitted to ICUs for severe COVID-19 despite this experience being considered traumatic in the literature. Methods The purpose of this case study is to describe the application of a four-session IRT for the treatment of COVID-related nightmares in a female patient after admission to the ICU. A 42-year-old Caucasian woman who recovered from a pulmonary rehabilitation program reported shortness of breath, dyspnea, and everyday life difficulties triggered by the long-COVID syndrome. She showed COVID-related nightmares and signs of post-traumatic symptoms (i.e., hyperarousal, nightmares, and avoidance of triggers associated with the traumatic situation). Psychological changes in the aftermath of a trauma, presence, and intensity of daytime sleepiness, dream activity, sleep disturbances, aspects of sleep and dreams, and symptoms of common mental health status are assessed as outcomes at the baseline (during the admission to pneumology rehabilitation) at 1-month (T1) and 3-month follow-up (T2). Follow-up data were collected through an online survey. Results By using IRT principles and techniques, the patient reported a decrease in the intensity and frequency of bad nightmares, an increase in the quality of sleep, and post-traumatic growth, developing a positive post-discharge. Conclusion Imagery rehearsal therapy may be effective for COVID-19-related nightmares and in increasing the quality of sleep among patients admitted to the ICU for the treatment of COVID-19. Furthermore, IRT could be useful for its brevity in hospital settings.